Predictors of persistent stress urinary incontinence after transvaginal mesh repair - Shohei Kawaguchi; Kazutaka Narimoto; Satoko Urata; Masami Takeyama; Yoshifumi Kadono; Atsushi Mizokami (BMC, 2018)
Abstract Background We evaluated the effect of transvaginal mesh (TVM) surgery for voiding function and continence using noninvasive examination and questionnaire. The present study aimed to ascertain which categories of patients need concomitant mid-urethral sling (MUS) after TVM surgery. Methods We included women who underwent TVM procedure between November 2009 and October 2013. Data from noninstrumented uroflowmetry and questionnaires about urinary symptoms were analyzed. Results The present study investigated the cases of 961 women who underwent TVM surgery. The persistence of stress urinary incontinence (SUI) was 57.6%. Almost all the parameters measured using uroflowmetry and questionnaires significantly improved in all types of urinary incontinence 12 months after surgery. A history of hysterectomy, preoperative high flow (corrected maximum flow rate > 1.5), and preoperative urge urinary incontinence were independent risk factors for the persistence of SUI. Conclusions TVM for pelvic organ prolapse improved subjective and objective voiding function. Mixed urinary incontinence (MUI) patients with high urinary flow may be suitable for concomitant MUS with TVM because of the high level of SUI persistence.